Exploring family caregiver burdens and coping mechanisms for patients with comorbid neglected tropical diseases and mental illness in Southern Ethiopia: insights from qualitative findings - Sidamo, Negussie Boti; Hebo, Sultan Hussen; Kassahun, Alemayehu Bekele; Endris, Bilcha Oumer (Frontiers in Tropical Diseases, 2025)
IntroductionMillions globally suffer from neglected tropical diseases (NTDs) and mental health conditions concurrently. Those with NTDs face heightened risks of mental health issues, and those with mental health conditions are more vulnerable to NTDs. Family caregivers of patients with both conditions often face significant burdens but are frequently overlooked as "hidden patients." Research on this issue is limited in Ethiopia.ObjectiveThis study explores the burdens and coping mechanisms of family caregivers for patients with comorbid NTDs and mental illness in Southern Ethiopia.MethodsThis qualitative phenomenological study engaged seventeen family caregivers of individuals with comorbid NTDs and mental illness. Participants were purposively selected to ensure the inclusion of individuals with rich, relevant experiences capable of providing profound insights into the phenomenon under study. To capture the in-depth experiences and perspectives of caregivers, semi-structured interviews were conducted in participants' homes or compound rooms, ensuring privacy and the prior acquisition of informed consent for audio-recording. The interviews were designed to provide a comfortable, natural setting conducive to open discussion. Transcripts were initially transcribed in Amharic and then translated into English, with each translation cross-verified against the original audio recordings to ensure accuracy. Data analysis followed an inductive thematic approach, allowing for themes and sub-themes to emerge organically from the data through multiple coding and validation cycles.ResultsCaregivers faced significant burdens in four main areas: physical, social, psychological, and economic. Physically, they undertook demanding tasks like bathing and feeding, leading to strain and health issues. Socially, they experienced isolation and stigma, impacting family contact and community participation. Psychologically, caregivers reported high stress, anxiety, and depression, compounded by managing both chronic conditions and societal stigma. Economically, they endured financial strain, including job loss or reduced working hours. Coping mechanisms included strong social support from family, friends, and community organizations, problem-solving techniques, self-care practices, and seeking emotional support.ConclusionCaregivers of patients with comorbid NTDs and mental illness in Southern Ethiopia experience substantial burdens across multiple dimensions. Effective coping mechanisms and robust social support are vital for alleviating these challenges and improving caregivers' well-being.